THE EFFECT OF DEBT COLLECTION EFFECTIVENESS ON THE LEVEL OF UNCOLLECTED RECEIVABLES AT PERUMDA MUARA TIRTA IN GORONTALO CITY - Iklima Putri Anggai; Ronald Soemitro Badu; Surya Handrisusanto Ahmad (Majapahit Journal of Islamic Finance and Management, 2026)
This study aims to analyze the effect of accounts receivable collection effectiveness on the level of uncollectible accounts at the Muara Tirta Regional Public Enterprise (Perumda) in Gorontalo City. The research method uses a quantitative approach with secondary data in the form of monthly financial reports for the period from January 2020 to December 2024 (60 observations). Collection effectiveness is measured using the Receivables Turnover Ratio (RTO), while the level of uncollectible receivables is proxied by the allowance for doubtful accounts ratio. The results of the study indicate that the effectiveness of accounts receivable collection has a negative and significant effect on the level of uncollectible accounts receivable. This indicates that the higher the accounts receivable turnover frequency, the lower the risk of uncollectible accounts receivable that the company must set aside.